Rare Intracardiac Tumor: Primary Cardiac Lymphoma Presenting as Atypical Angina - Karthigesu Aimanan; K. Saravana Kumar; M. N. Mohd Arif; Md Noor Zuraini; Md Jamil Ramdzan; L. Hamdan (Case Reports in Medicine)
Primary lymphomas of the heart are extremely rare, accounting for 2% of all primary cardiac tumors. Due to the rare presentation, there is no proper consensus available on treatment strategy. Preoperative confirmation of the pathology is fundamental in guiding an early treatment plan, which allows for improved prognosis. Unfortunately, in most cases, primary cardiac lymphoma is only identified on postoperative histopathological analyses, which affect the treatment plan and outcome. Here, we report a unique case of primary cardiac lymphoma presented with dyspnea and reduced effort tolerance. Young age, rapid onset of symptom, and absence of cardiac risk factors prompted us towards further imaging and emergency resection. The patient received a course of postoperative chemotherapy and was disease-free on six months of follow-up.